Characterization of enamel after the use of oral hygiene auxiliaries with whiteners = Caracterización del esmalte después del uso de auxiliares de higiene bucal con blanqueadores - Zavala Alonso, Norma Verónica; Ramírez González, Jorge Humberto; Ramírez Vergara, Mariana; Roque Márquez, José Gilberto; Silva-Herzog Flores, Daniel (2019)
The purpose of this study was to evaluate the effect of the use of the combined auxiliaries of oral hygiene with whitening agents on the micro-hardness and micro-morphology of dental enamel. Materials and Methods. 40 human incisors were used and sectioned to obtain 4x4mm samples and divided into four study groups. Group 1: Electric brushing with Toothpaste (BTP); Group 2: Electric brushing with Toothpaste+mouthwash (BTP+MW); Group 3: Electric brushing with Toothpaste+whitening pen (BTP+WP); Group 4: Electric brushing with Toothpaste+mouth wash+whitening pen (BTP+MW+WP). Samples were submitted toVickers micro-hardness test and visualized using scanning electron microscopy (SEM). Results. All groups, with the exception of group 1, showed a decrease in micro-hardness values after applying the treatments (p<0.05). Likewise, when comparing the values after the treatments between the groups, significant statistical differences were found in all of comparisons except for those of groups 2 and 4. SEM images showed changes in the morphology in all the study groups with the exception of group 1. Conclusion. Significant changes such as decrease in micro-hardness as well as in the topography of the enamel surface such as elevations, craters, porosities and etching patterns were founded after the use of the combination of auxiliaries of oral hygiene with whitening agents.
El propósito de este estudio fue evaluar el efecto del uso de los auxiliares de higiene oral combinados con agentes blanqueadores sobre la microdureza y la micro-morfología del esmalte dental. Materiales y métodos. Se utilizaron 40 incisivos humanos y se seccionaron para obtener muestras de 4x4 mm los cuales se dividieron en cuatro grupos de estudio. Grupo 1: cepillado eléctrico con pasta de dientes (BTP); Grupo 2: cepillado eléctrico con pasta dental+enjuague bucal (BTP+MW); Grupo 3: cepillado eléctrico con pasta dental+pluma blanqueadora (BTP+WP); Grupo 4: cepillado eléctrico con pasta dental+enjuague bucal+pluma blanqueadora (BTP+MW+WP). Las muestras fueron analizadas por medio de microdurezaVickers y microscopía electronica de barrido (SEM). Resultados. Todos los grupos, con la excepción del grupo 1, mostraron una disminución en los valores de microdureza después de aplicar los tratamientos (p<0.05). Del mismo modo, al comparar los valores después de los tratamientos entre los grupos, se encontraron diferencias estadísticamente significativas en todas las comparaciones, excepto en las de los grupos 2 y 4. Las imágenes de SEM nos muestran cambios en la morfología en todos los grupos de estudio con la excepción del grupo 1 Conclusión. Cambios significativos como la disminución de la microdureza y los cambios en la topografía de la superficie del esmalte, como elevaciones, cráteres, porosidades y patrones de grabado, se encontraron después del uso de la combinación de auxiliares de la higiene oral con agentes blanqueadores.
En revista Odóvtos, vol. 21, no. 3 (septiembre-diciembre 2019)
Descripción basada en el contenido visto 05 de septiembre, 2024
También disponible en formato HTML y EPUB